Modelling of cycling of lithium battery with microporous carbon electrode - Portnyagin, D. (Condensed Matter Physics, 2008)
Charge/discharge cycles of lithium cell with microporous carbon electrode under potentiodynamic control have
been modelled. Predictions of the models with variable and constant diffusion coefficient neglecting the electric
field inside the particle (CPM, DFM) are compared to the predictions of the models with variable and constant
diffusion coefficient in which electrostatic interaction inside the particles of carbon electrode (CPME, DFME)
is taken into account. There is observed a considerable difference between both. Electrostatic interactions
of lithium ions with each other and the charge distributed inside the particle promote intercalation during the
discharge of the cell and deintercalation during the charge. The dependance of the effect of hysteresis during
the cycling of the cell on the rate of change of the applied voltage is studied. The larger is the speed of change
of the applied voltage the more effective is hysteresis. We have also obtained concentration profiles at different
stages of charge/discharge process. Чисельно моделювалися розрядно/заряднi цикли лiтiєвої батареї iз вуглецевим мiкропористим електродом в режимi заданої напруги. Порiвнювалися передбачення двох видiв моделей: з постiйним та змiнним коефiцiєнтом дифузiї без врахування електростатичного поля, та з постiйним та змiнним коефiцiєнтом дифузiї з електростатичною взаємодiєю мiж iонами лiтiю та iз розподiленим зарядом всерединi частинок вуглецевого електрода. Спостерiгалася певна розбiжнiсть мiж ними. Електростатична взаємодiя сприяє iнтеркаляцiї пiд час розрядки батареї та деiнтеркаляцiї пiд час зарядки. Вивчалася залежнiсть вираженостi гiстерезису вiд швидкостi змiни прикладеної напруги. Гiстерезис проявляється тим бiльше, чим бiльша швидкiсть прикладеної напруги. Було також отримано профiлi концентрацiї на рiзних стадiях процесу розрядки/зарядки.